PHYTOGENIC 'GREEN SYNTHESIS' OF SILVER NANOPARTICLES WITH ENHANCED ANTIBACTERIAL AND ANTI-CANCER ACTIVITY - D. K. MARAVI; A. K. SAHOO; U. GOSWAMI; D. S. PRASAD; L. SAHOO; S. S. GHOSH (International Journal of Pharma and Bio Sciences, 2015)
Phytogenic ‘green synthesis’ of the Ag NPs offers huge promises as the process is environmentally benign, economical and scalable. Herein, we demonstrate an one step, easy and eco-friendly method for synthesis of Ag NPs-composites (Ag NPs-plant extract) by using the extract of Jatropha curcas as reducing as well as stabilizing agent. The composites were characterized by UV-Vis spectroscopy, transmission electron microscopy (TEM), selected area electron diffraction (SAED) and Fourier transform infrared spectroscopy (FTIR) analysis. The green fluorescent protein expressing E.coli was used as an exemplary to study the anti-bacterial activity and establish the mechanism of action of these nano-composites. Our results demonstrate that cell wall perforation is the primary reason of non-viability of the bacterial cells as there is no direct effect of Ag NPs-composite on cellular DNA. Further, the cytotoxicity test of Ag NPs-composites against the HeLa cells revealed the potential of these Ag NPs composites for use as cancer therapeutic agents.